Osteoarthritis, coronary artery disease, and myocardial infarction: A mendelian randomization study - Xu, Huiqing; Ling, Yuxiao; Jiang, Han; Li, Yingjun; Jiang, Minmin (Frontiers in Cardiovascular Medicine, 2022)
Background. Observational studies indicate that osteoarthritis (OA) and coronary artery disease (CAD), as well as myocardial infarction (MI), are often diagnosed as comorbid diseases. We performed bidirectional Mendelian randomization (MR) study to demonstrate whether there is a causal relationship between OA, CAD, and MI. Methods. We extracted single nucleotide polymorphisms (SNPs) related to OA in the Genetics of Osteoarthritis (GO) Consortium as instrumental variables to assess whether OA is associated with CAD and MI in the CARDIoGRAMplusC4D 1000 Genomes genome-wide association study (GWAS). In the reverse MR, we used CAD-associated and MI-associated SNPs to the GWAS of OA to analyze their causality. These GWASs included 766,690 individuals of OA, 184,305 individuals of CAD, and 166,065 individuals of MI. MR was conducted using several methods, including inverse variance weighted (IVW), weighted median, MR-Egger, and MR-PRESSO method. Results. The forward causal effect of OA on CAD and MI was not observed. In reverse analysis, no causal effect was discovered for CAD on the risk of OA. Notably, we observed a causal association between MI and total OA [IVW odds ratio (OR) = 0.95, 95% confidence interval (CI) = 0.93, 0.98, P = 4E-04] and spine OA (IVW OR = 0.92, 95% CI = 0.88, 0.97, P = 0.001), but a null association between MI and knee OA, hip OA, hand OA and thumb OA. Conclusions. This MR study identifies a potentially protective effect of genetically predicted MI on total and spine OA risk.